Analysis of interleukin-17 and interleukin-23 for estimating disease activity and predicting the response to treatment in active lupus nephritis patients - Dedong, Huang; Feiyan, Zhu; Jie, Shi; Xiaowei, Lai; Shaoyang, Wang (Immunology letters, 2019)
•IL-17 and IL-23 may involve and contribute to lupus nephritis.•IL-17 could be used as a biomarker for lupus nephritis clinical and pathological active index.•IL-23 could be used as a predictor for predicting response to treatment in patients with active lupus nephritis. Renal biopsy is a “gold standard” for establishing the diagnosis and assessing prognosis and monitoring therapy in lupus nephritis (LN) patients, but it is an invasive and inconvenient procedure. Evidences showed that interleukin-17(IL-17) and interleukin-23(IL-23) may be as alternative biomarkers for diagnosing LN, monitoring LN activity and predicting the response to treatment of LN. To analyze the roles of IL-17 and IL-23 in evaluation activity of LN and predicting active LN response to immunosuppressive treatment, by comparison between IL-17, IL-23 and clinical data of LN. Eighty patients with LN and 20 healthy volunteers were enrolled in this study. Plasma levels of IL-17 and IL-23 were detected by ELISA and clinical data were collected in patients with LN. Thirty-seven patients with active LN accepted immunosuppressive therapy and followed up to 6 months. The roles of IL-17 and IL-23 in evaluation the activity of LN and the predictability for active LN response to immunosuppressive treatment were analyzed. The ages or gender rations between LN patients and healthy controls were not significant difference at baseline. Baseline levels of IL-17 and IL-23 were higher in patients with active LN compare to them in patients with inactive LN or controls (P<0.001) and IL-23 in patients with inactive LN was higher than its in controls (P=0.004). IL-17 and IL-23 decreased significantly in active LN patients after 6 months therapy (P<0.001). The baseline level of IL-23 was significantly different in subgroups response to the immunosuppressive treatment in patients with active LN (P=0.0014). Baseline level of IL-23 in complete response group was lower than its in partial response group (P=0.0015) or nonresponse group (P=0.013). IL-17 was negative correlation with C3 (r=-0.44, P<0.001). IL-17 and IL-23 correlated with systemic lupus erythematosus (SLE) disease activity index (P<0.001). The correlation between IL-17 and LN pathological acute index (AI) was higher than the correlation between IL-23 and AI. (r=0.52, P<0.001 vs. r=0.41, P<0.001). Receiver Operation Characteristics (ROC) showed that IL-17 and IL-23 could be used to evaluate SLE disease activity index. IL-17 could be used as biomarker to evaluate pathological AI. IL-23 could be used as a predictor for predicting response to immunosuppressive treatment in patients with active LN. IL-17 and IL-23 may involve and contribute to LN. IL-17 could be used as a biomarker for LN clinical and pathological AI. IL-23 could be used as a predictor for predicting response to immunosuppressive treatment in patients with active LN.